Biocompatibility of PMMA-based material implanted in bone tissue - Karadžić Branislav 1; Bojović S.; Dražić Radojica (Serbian Medical Society - Dental Section, Belgrade, 2004)
The aim of histopathological investigations was to evaluate the effect of PMMA based material on bone tissue of experimental animals. In the femoral bone of laboratory Wistar rats pastes were implanted for canal obturation SEALPEX (Kerr, Romulus, USA), AH-26 (DeTrey, Zurich, Switzerland) and poly methyl metacrylate (PMMA) based material, called SPONGI CEMENT (Tomic, 1981, US PATENT 4296209). As control material sterile wax was used. The rats were sacrificed 60 days after implantation, and the material was prepared by standard histological method and hematoxillin eosine stained. The results of microscopic investigations suggested that implanted PMMA based material was in direct contact with the new completely formed bone. SEALPEX and AH-26 implanted in bone tissue of rats was surrounded with inflamed infiltrate. Implantation of wax produced fibrous tissue capsule around the material. These findings suggest biocompatibility of polymethyl metacrylate material (PMMA).